Music, technology and hegemony: César Bolaños and the transgressions of popular music - Alvarado Manrique, Luis Alberto (2024)
The following text presents some ideas of the composer César Bolaños, expressed in an interview and an article from the mid-70s and early 80s, respectively, which offer some keys to understand Bolaños' opposition to a hegemonic model of the use of technology in musical creation. This opens another perspective for understanding his departure from musical composition in the 70s after returning to Peru after ten years of living in Argentina, as well as the development of music with electronic media in Peru.